Arthropod diversity in Iran: Class Diplopoda Blainville in Gervais, 1844 - Sergei I. Golovatch (Journal of Insect Biodiversity and Systematics)
Formally, the diplopod fauna of Iran presently contains 54 species from 27 genera, 13 families and eight orders, all listed and supplied with nomenclature, diversity estimates and known species records. Endemism is profound at the species level (CA 80%), but nearly absent at any higher rank. The only and quite remarkable exception is the genus Chiraziulus, both species of which are endemic to southern or central Iran. The fauna can generally be considered as Caucasian, part of the eastern Mediterranean realm, vs Chiraziulus that clearly represents a very ancient and relict group (suborder Cambalidea) presently occurring in the Nearctic (together with the Hawaiian Islands, Pacific Ocean) in the New World, but rather Oriental, both tropical and subtropical, in Indo-Australasia (together with the Mascarene Islands, Indian Ocean).